Optimization of Filter-aided Sample Preparation Method Based on High-resolution Mass Spectrometry - Ying ZHANG; Xuan SUN; Ling-jie MENG (Zhipu Xuebao)
This study centered on an improved filter-aided sample preparation (FASP) method for proteomic sample preparation. The main strategy focused on changing the chemical and physical properties of regenerated cellulose (RC) membranes in ultrafiltration tubes to reduce the loss of protein sample due to non-specific absorption on the membranes. Firstly, the RC membrane was immersed in isopropanol for the activation, followed by immersion in a 6% NaOH solution for the alkalization. Then, the amphiphilic small molecule glycine was grafted onto the surface of the activated RC membrane to enhance its hydrophilicity. The regenerated ultrafiltration membrane was characterized from multiple perspectives. The electron microscopy showed that the membrane structure and pore size remained unchanged after modification, the Raman spectroscopy coupled with X-ray photoelectron spectroscopy (XPS) demonstrated that glycine was successfully grafted onto the surface of the regenerated cellulose membrane, the hydrophilicity test indicated a decrease in the contact angle of the modified membrane, suggesting enhanced hydrophilicity. The protein adsorption test showed a reduction in bovine serum albumin (BSA) protein adsorption on the modified membrane, thus minimizing protein sample loss. When using this improved FASP method with Q Exactive™ Plus for LC-MS/MS analysis of HeLa cells, compared with the traditional FASP method and the in-solution digestion method, it was found that the improved FASP method, which is applicable to three types of lysis buffers (NP40, SDS, and Triton X-100), can increase the number of identified proteins by approximately 7%-9% and the number of identified peptides by approximately 30%-40%. Besides, the improved FASP method also has advantages in terms of peptide abundance distribution. For instance, it can detect more peptides with an abundance greater than 104 compared with the traditional FASP method and more peptides with an abundance greater than 106 compared with the in-solution digestion method, along with better reproducibility. Moreover, the improved FASP method shows no bias for identifying proteins with different molecular weights and isoelectric points, and its optimal protein loading is determined to be 20 μg. The developed method can reduce protein loss during sample preparation, especially for the precious trace samples. This is helpful for screening disease biomarkers, exploring drug efficacy mechanisms, identifying effective targets, and promoting the diagnosis, monitoring, and treatment of diseases. However, as the study did not clearly specify the limitations of this method, further exploration can be conducted to assess whether this method can be applied to different types of cells or more complex disease research.